(untitled) (Research, Society and Development, 2024)
Fish are known for their diversity and plasticity in sex determination mechanisms, which sets them apart among vertebrates. This study aims to conduct a scientometric review of research on sex determination in fish, with a special focus on the pirarucu (Arapaima gigas) a species of great aquaculture importance, whose sex determination and differentiation mechanisms are still unknown. To achieve this objective, a bibliographic survey was conducted on the Web of Science database, using keywords and Boolean operators such as "sex determination AND fish", "sex-specific marker AND fish", "sex identification AND fish", and "sex identification AND Arapaima gigas", for the period from 2000 to 2020. As a result, 80 articles from 22 countries were analyzed. China accounted for the largest volume of publications, totaling 31 articles. The study identified 35 families and 75 fish species, with emphasis on commercially important ones. A significant increase in studies was observed from 2017 to 2020, primarily due to the growing use of next-generation sequencing (NGS) technologies. Regarding the pirarucu, 10 publications were found, but to date, there is no completely efficient and accessible method for the sexual identification of this species. These findings provide valuable insights into the current state of research on sex determination in fish, highlighting areas of progress and the need for future investigations to enhance knowledge in this specific area.